Letter of authorisation - Trades Union Congress ; Labour Party (Great Britain)
1936-08-21 21st August 1936. TO WHOM IT MAY CONCERN. The bearer of this letter, John R. Watkins, is the fully authorised special photographer of the Daily Herald, British Labour Newspaper. The International Federation of Trade Unions, the Labour and Socialist International, and the British National Council of Labour strongly urge that he be granted all possible facilities to obtain photographs from Spanish Government angle for publication in the Daily Herald. All the photographs available in London newspapers so far are from the rebel side. Signed (President of the I.F.T.U. and (Secretary of the British T.U.C. Secretary of the British Labour Party. 292/946/10/135